Law Enforcement Against Unscrupulous Health Workers Who Inject Empty Vaccines to Vaccine Recipients - Nopesius Bawembang; Johanis LSS. Polii; Janesandre Palilingan; R. Rigen I. Sumilat; Grenaldo Ginting (International Journal Labs, 2023)
The COVID-19 pandemic has resulted in millions of people dying from the virus and has affected various sectors such as education and the economy, therefore efforts are needed to overcome this pandemic, including vaccines with the aim of increasing herd immunity. However, efforts to overcome this outbreak have unscrupulous nurses who recommend empty vaccines. This research aims to determine law enforcement efforts against unscrupulous health workers who inject empty vaccines into vaccine recipients. This research uses the research method of literature study. Data collection techniques in this research are obtained from books, journals, and other relevant information from Google Scholar for the period 2013-2023 with several search keywords. The results showed that nurses injecting empty vaccines in an effort to overcome the COVID-19 pandemic that deliberately hampered the implementation of pandemic mitigation were threatened with imprisonment for a maximum of 1 year and/or a maximum fine of Rp1 million. However, if the vaccine injection occurs due to negligence, the perpetrator is threatened with imprisonment for a maximum of 6 months and/or a fine of up to Rp. 500 thousand.